MK2 drives progression of pancreas and colon cancers by suppressing CD8+ T cell cytotoxic function and is a potential immunotherapy target - Jacenik, Damian; Lebish, Eric J.; Beswick, Ellen J. (Frontiers in Immunology, 2023)
Background Immune cell composition is a critical and dynamic component of the tumor microenvironment, which has an impact on immunosuppression and progression of cancer. T cells, especially CD8+ T cells, are one of the major immune cell types responsible for tumor cell killing employing receptor-ligand mediated apoptosis and/or releasing lytic granules among others. Accumulating evidence highlighted that adoptive transfer of activated and/or modified immune cells can enhance anti-tumorigenic immune responses and serve as promising therapy approach for patients with cancers. The mitogen-activated protein kinase-activated protein kinase 2 (MK2) is a serine/threonine protein kinase, which controls production and secretion of numerous pro-inflammatory cytokines and chemokines involved in tumorigenesis. However, limited efforts have been made to learn how MK2 may affects CD8+ T cell action and function in the tumor microenvironment especially in gastrointestinal cancers. Methods To explore the therapeutic potential of MK2 in the immune response mediated by CD8+ T cells, RAG1 knockout mice with PK5L1940 and BRAF cells-derived allograft tumors were treated with WT or MK2 knockout CD8+ T cells. The phenotype of CD8+ T cells with MK2 depletion were evaluated in vitro. Immunofluorescence staining, real-time PCR and multiplex analysis were utilized to estimate the expression of apoptotic and lytic factors. Results Here, we show that CD8+ T cells with MK2 depletion prevent gastrointestinal cancer growth, which is accompanied by enhanced expression and secretion of factors related to apoptosis. Moreover, using in vitro and in vivo approaches, we found that depletion of MK2 lead to hyperactivation of CD8+ T cells and enhanced anti-tumor immunity. Conclusion Overall, we documented that MK2 drives the progression of gastrointestinal cancers and prevents immune response generated by CD8+ T cells suggesting potential implications of MK2 in the immunotherapy of gastrointestinal cancers.